DETECÇÃO DO NOROVÍRUS GII EM CRIANÇAS DE ATÉ 5 ANOS DE IDADE NO MUNICÍPIO DE GUARAPUAVA-PR - SEMAAN, LENI MACEDO (2014)
For a long time, the Norovirus diagnosis (NoV) was impaired by the absence of an experimental animal model, and because it isn´t detectable in cell culture. Although, with advances in molecular techniques, the NoV has gained great importance in the gastroenteritis. Studies report that, after the development of the vaccine against rotavirus, the NoV has been emerging as the main etiological agent. Few studies in Brazil have investigated the circulation of NoV, and most of them are in closed places (hospitals, nursing homes, and day care centers), and few of them report the circulation in the community. This study aimed to show the circulation of this virus in children enrolled in the public health system of Guarapuava-PR, from March 2011 to February 2012. It was collected 120 fecal samples from children up to 5 years old, analyzed by polymerase chain reaction (RT-PCR) specific for NoV GII, as this is the genotype that stands out most in Brazil and in the world. Optimized RT-PCR assay and apply to 120 collected samples, with NoV detected in 19, accounting for 15,83%. The months with the largest circulation were September and October 2011, suggesting the possibility of an outbreak during this period. These findings indicate that NoV is circulating in the community children as an agent of gastroenteritis, should now be considered in the differential diagnosis and in the institution of measures to control transmission.